The inﬂuence of religious orientation on viewers’ loyalty towards satellite TV channels the case of Muslim viewers - Abu-Alhaija, Ahmad Saifalddin; Raja Yusof, Raja Nerina; Hashim, Haslinda; Jaharuddin, Norsiah (Emerald Publishing, 2019)
Purpose This paper aims to examine the influence of religious orientation on viewers’ loyalty, viewers’ satisfaction and perceived content quality; to examine the influences of perceived content quality and viewers’ satisfaction on viewers’ loyalty; and to examine the mediating roles of perceived content quality and viewers’ satisfaction. Design/methodology/approach A set of questionnaires was distributed to 750 respondents in Jordan using convenience sampling. The data were analysed using structural equation modelling. Findings The following are the findings: religious orientation has a direct positive influence on viewer’s loyalty, viewer’s satisfaction and perceived content quality; perceived content quality has a positive influence on viewer’s satisfaction; viewer’s satisfaction has positive influence on viewer’s loyalty; perceived content quality does not have any direct influence on viewer’s loyalty; perceived content quality has partial mediation role in the relationship between religious orientation and viewer’s satisfaction, while viewer’s satisfaction has full mediation role in the relationship between perceived content quality and viewer’s loyalty. Originality/value It is different from the previous studies that mostly focussed on religious commitment and religiosity as the important predictors of customer’s loyalty, and this study emphasised on the influence of religious orientation (the motivational approach of religion) as one of the religious dimensions that can affect customer’s loyalty model. The selected approach may provide additional insights into the existing loyalty models.